Master Plan UMKM Berbasis Perikanan untuk Meningkatkan Pengolahan Produk Ikan yang Memiliki Nilai Tambah Tinggi - Riana, I Gede; Wiagustini, Ni Luh Putu; Meydianawathi, Luh Gede (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 2, Agustus 2014 (pp. 83-198), 2015)
This research aims to generate a Master plan of fisheries-based SME development concept in Bali region, in order to build Bali as the centre for production and processing of fishery products in the Coridor of Bali-Nusa Tenggara. In Year-1 of the study period, the research activities carried out includes three processes, including analysis of the potensial of SMEs, analyzes the business cycle, and identification of barriers and chalenges. By using the method of linear regression analysis, Geographic Information System (GIS) and Analytical Hierarchy Process (AHP), the study result in Year-1, obtained some information about characteristics of fisheries based SMEs Bali, consisting of: 1) there is positive effect between GDP growth and energy work on the level of productivity (output value) of SMEs; 2) the need for development of fisheries-based SMEs in Bali include some operational, capital, and market access aspects. To the Bali Provincial Government, SMEs and the poblic are expected to synergize themselves, in term of institutionally, improving the quality of human recources, empowering financial institutions at the local level, as well as active participation in marketing access to the international level.
Keywords: Fisheries-based SME; value added, acceleration of economic development; coastal communities